Conjunctival rhinosporidiosis presenting as a cystic mass-an unusual presentation - Lavaju, P; Arya, SK; Kumar, B; Upadhaya, P (Nepalese Journal of Ophthalmology, 2010)
Rhinosporidiosis is endemic in India and Sri Lanka and parts of East Africa and South America. Cases of ocular rhinosporidiosis have also been reported from Nepal. Ocular rhinosporidiosis usually involves the conjunctiva and the lacrimal sac. It usually presents as a polypoidal mass. Cystic mode of presentation has not yet been reported in the literature. We herein report an unusual mode of presentation of ocular rhinosporidiosis presenting as a huge conjunctival cystic mass. Key words: conjunctival cyst; oculosporidiosis; rhinosporidiosis; Rhinosporidiosis seeberi DOI: 10.3126/nepjoph.v2i2.3724 Nep J Oph 2010;2(2) 157-159